Editorial Cartoons as Mirror of the Nigerian Nation: The Example of New Telegraph - Ogazie, Charles; Odetade , Ibitayo Odekunle (International Journal of Language and Literary Studies, 2020)
It is very obvious that newspapers do not just report news, make known governmental policies or educate people on the happenings in societies among other things (Ogazie 2012). It however, serves as a watch dog in society. As the press beams its search light on the activities of government through its reportage, the public is made to participate in the process of governance and at the same time, aligns the governed to come to terms with the state of the nation. In a pluralistic nation like Nigeria where the heterogeneous populace is exposed to diverse media content, senders of information, especially those of the print media, convey socio-political, economic, educational coupled with religious messages in a unique, blunt, creative but satirical manner without naming names. This paper asserts that this unique function is best left at the door step of the editorial cartoonists who through their metaphorical codification sketches, drawings or impressions, tell a verisimilitude tale of the state of the nation. Through content analysis of selected cartoons in New Telegraph Newspaper, the paper concludes that editorial cartoons can be seen as a viable and powerful reflective medium via which national issues are raised in an imaginary court for public debate and as such erect a positive signpost towards reconstructing, developing and sustaining the polity for the betterment of all.